Adopting electronic payment tools to enhance capacity Banks attract public savings: Applied research on a sample of Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the impact of adopting electronic payment tools on the ability of Iraqi banks to attract public savings. The study is based on the hypothesis that the use of these electronic tools contributes to increasing the volume of savings in banks. The financial data of Iraqi banks for the period (2017) - 2022) are analyzed to analyze the relationship between payment and savings tools. The results showed a significant positive relationship between electronic payment tools and the volume of savings, as electronic payment tools contributed to a significant increase in the volume of deposits. It also showed a large discrepancy between deposits in government and private banks.